Encounters: Relationship in the Study and Teaching of Literature - Christina Vischer Bruns (Journal of the Assembly for Expanded Perspectives on Learning, 2003)
While trends in the teaching of literature of the last few decades may seem at odds with one another, the thread that can weave them together is a recognition of relationship among readers, text, author, and other readers.